Increased GABA contributes to enhanced control over motor excitability in Tourette syndrome - Draper, A; Stephenson, M; Jackson, G; Pépés, S; Morgan, P; Morris, P; Jackson, SR (Cell Press, 2014)
Summary: Tourette syndrome (TS) is a developmental neurological disorder characterized by vocal and motor tics [1] and associated with cortical-striatal-thalamic-cortical circuit dysfunction [2 and 3], hyperexcitability within cortical motor areas [4], and altered intracortical inhibition [4, 5, 6 and 7]. TS often follows a developmental time course in which tics become increasingly more controlled during adolescence in many individuals [1], who exhibit enhanced control over their volitional movements [8, 9, 10 and 11]. Importantly, control over motor outputs appears to be brought about by a reduction in the gain of motor excitability [6, 7, 12 and 13]. Here we present a neurochemical basis for a localized gain control mechanism. We used ultra-high-field (7 T) magnetic resonance spectroscopy to investigate in vivo concentrations of γ-aminobutyric acid (GABA) within primary and secondary motor areas of individuals with TS. We demonstrate that GABA concentrations within the supplementary motor area (SMA)—a region strongly associated with the genesis of motor tics in TS [14]—are paradoxically elevated in individuals with TS and inversely related to fMRI blood oxygen level-dependent activation. By contrast, GABA concentrations in control sites do not differ from those of a matched control group. Importantly, we also show that GABA concentrations within the SMA are inversely correlated with cortical excitability in primary motor cortex and are predicted by motor tic severity and white-matter microstructure (FA) within a region of the corpus callosum that projects to the SMA within each hemisphere. Based upon these findings, we propose that extrasynaptic GABA contributes to a form of control, based upon localized tonic inhibition within the SMA, that may lead to the suppression of tics.